Rancang Bangun Computer Based Test (CBT) Berbasis Web - Ulum, Mohammad Nurul; Hidayat, Syarif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Examinations are an evaluation method in the teaching and learning process in schools. Generally, exams in schools are still carried out conventionally using paper and stationery, and exam assessments are carried out directly by the teacher. However. The process of creating exam questions, duplicating questions, evaluating and filling in answers is still manual using paper and stationery, causing various obstacles such as high costs and long correction times. To solve the problem above, the researcher used the Agile system development method with the Extreme Programming model which involves four stages: planning, designing, coding and testing. The research results show the success of the CBT application that was built. The application was tested using the black box testing method. Test results show that the correction process is faster by 0.9 seconds and more accurate. Apart from that, in terms of costs, using this application is also cheaper. This shows that the CBT application has a positive impact in increasing the efficiency, accuracy and effectiveness of testing and reducing the costs of administering the exam.